Larrea tridentata Extract Mitigates Oxidative Stress-Induced Cytotoxicity in Human Neuroblastoma SH-SY5Y Cells - Karla Morán-Santibañez; Abimael H. Vasquez; Armando Varela-Ramirez; Veronica Henderson; Janae Sweeney; Valerie Odero-Marah; Karine Fenelon; Rachid Skouta (MDPI AG, 2019)
Creosote bush (Larrea tridentata; LT) leaves extracts were tested for their potential efficacy to mitigate cellular oxidative stress on human SH-SY5Y cells. Here, the differential nuclear staining assay, a bioimager system, and flow cytometric protocols, concurrently with several specific chemicals, were used to measure the percentage of cell viability and several facets implicated in the cytoprotective mechanism of LT extracts. Initially, three LT extracts, prepared with different solvents, ethanol, ethanol:water (e/w), and water, were tested for their capacity to rescue the viability of cells undergoing aggressive H2O2-induced oxidative stress. Results indicate that the LT extract prepared with a mixture of ethanol:water (LT-e/w; 60:40% v/v) displayed the most effective cytoprotection rescue activity. Interestingly, by investigating the LT-e/w mechanism of action, it was found that LT-e/w extract decreases the levels of H2O2-provoked reactive oxidative species (ROS) accumulation, mitochondrial depolarization, phosphatidylserine externalization, caspase-3/7 activation, and poly (ADP-ribose) polymerase (PARP) cleavage significantly, which are hallmarks of apoptosis. Thus, out of the three LT extracts tested, our findings highlight that the LT-e/w extract was the most effective protective reagent on SH-SY5Y cells undergoing oxidative stress in vitro, functioning as a natural anti-apoptotic extract. These findings warrant further LT-e/w extract examination in a holistic context.